Dopaminergic Modulation of Corticostriatal Responses in Medium Spiny Projection Neurons from Direct and Indirect Pathways - Flores-Barrera, Edén; Vizcarra-Chacón, Bianca J.; Bargas, Jose; Tapia, Dagoberto; Galarraga, Elvira (Frontiers in Systems Neuroscience, 2011)
Suprathreshold corticostriatal responses recorded from medium spiny neurons (MSNs) from the direct and indirect pathways of the basal ganglia are different. Their differences readily distinguish D1- and D2-type receptor expressing MSNs in both BAC-transgenic mice and their control littermates as well as in rats: Indirect pathway neurons are more excitable than direct pathway neurons revealing autoregenerative spikes underlying their spike trains, whereas direct pathway neurons exhibit more prolonged plateau potentials and spike trains. SFK 81297, a selective agonist for D1-class receptors enhanced corticostriatal responses in direct pathway neurons, while quinelorane, a selective agonist for D2-class receptors reduced orthodromic and autoregenerative responses in indirect pathway neurons thus making both neuron classes similarly excitable. Because dopaminergic postsynaptic actions target CaV1 (L) class voltage-gated calcium channels in MSNs, we hypothesized that these channels are involved and can explain a part of the dopaminergic actions on corticostriatal integration. Both 2.5 M nicardipine and 400 nM calciseptine, selective CaV1 channel blockers, reduced corticostriatal responses in both D1- and D2-receptor expressing neurons, respectively. A previous blockage of CaV1 channels occluded the actions of dopamine agonists in both neuronal classes. In contrast, a CaV1 (L) channel activator, 2.5 M Bay K 8644, enhanced corticostriatal responses in neurons from both pathways. It is concluded that CaV1 intrinsic currents mediate a part of the dopaminergic modulation during orthodromic synaptic integration of cortical inputs in both classes of MSNs.